(untitled) (African Journal of Biomedical Research, 2020)
The Center for Population and Reproductive Health, College of Medicine, University of Ibadan, Ibadan, Nigeria , with support from its NIH Planning Grant organized a two Day workshop on “Ethics and Responsible Conduct of Research” at the University of Ibadan Centre for Sustainable Development (CESDEV). There were 8 facilitators and 78 participants. The workshop concluded that responsible conduct of research (RCR) is the practice of scientific investigation or research with integrity involving but not limited to the awareness and application of established professional norms and ethical principles in the performance of all activities related to scientific research